Hedgehog and Fox: Anderson as Historian and Philologist - Sommer, Benjamin D. (Harvard theological review, 2010)
To sin or transgress, according to one dictionary definition, is to go beyond a limit, to cross what is supposed to be a clear border. In this sense, one can say that Gary Anderson has succeeded in writing a very sinful book. Like Sennacherib as the rabbis describe him, Anderson is (he “erases boundaries between nations”)—only I use this phrase to describe Anderson in rather a more positive sense than the rabbis intended it when they applied it to the Assyrian emperor.2 Throughout this book we are discussing, Anderson crosses boundaries between academic disciplines: biblical criticisms that study the Hebrew Bible and the New Testament, Qumranic scholarship, rabbinics, patristics, the study of both medieval Catholic and early Protestant theology. He crosses boundaries within some of these fields, as well: for example, by attending to modern Israeli biblical scholarship in a way that is, alas, all too rare among non-Jewish scholars in North America and Europe; or by showing scholars of rabbinics what they can learn from the study of the New Testament, especially when that study is conscious of its roots in medieval and early modern theology. Most importantly, Anderson tears down artificial barriers that separate historical, philological, descriptive scholarship on the one side from constructive theology and inter-religious dialogue on the other.